„Lwowskie piosenki uliczne, kabaretowe i okolicznościowe do 1939 roku” jako źródło badań nad muzyką miejską we Lwowie - Olijnyk, Iwanna (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
Lviv, as one of the cultural centers of Eastern Europe at the beginning of the 20th century became the object of many studies in the academy music field. The study of music collections opens the way of reproducing the authentic sound of urban songs and also the main intonation parameters of the musical world of Lviv. The publication of texts and sheet music of Lviv urban songs dates back to the turn of the 19th and 20th centuries. In 1989 appeared the collection, which became the most complete and correct edition of Lviv city songs for that time – „Lwowskie piosenki uliczne, kabaretowe i okolicznościowe do 1939 rokuˮ, created by a tandem of well-known Polish scientists - musicologist Jerzy Habela and philologist Zofia Kurzowa. The collection contains 151 songs, which are divided into 7 sections, where each song is accompanied by comments on previous versions of its publications, possible versions of the song's origin, as well as explanations of the lexical meanings of phrases. Thanks to the careful fixation of musical texts, the collection became a highquality material for further research in the direction of intonation analysis, in particular, the determination of melodic formulas of the city music of Lviv.